European guidelines for workplace drug testing in oral fluid. Issue 3 (27th October 2017) - Brcak, Michaela; Beck, Olof; Bosch, Tessa; Carmichael, Duncan; Fucci, Nadia; George, Claire; Piper, Mark; Salomone, Alberto; Schielen, Wim; Steinmeyer, Stefan; Taskinen, Sanna; Weinmann, Wolfgang
Abstract: These guidelines for Legally Defensible Workplace Drug Testing have been prepared and updated by the European Workplace Drug Testing Society (EWDTS). The European Guidelines are designed to establish best practice procedures whilst allowing individual countries to operate within the requirements of national customs and legislation. The EWDTS recommends that all European laboratories that undertake legally defensible workplace drug testing should use these guidelines as a template for accreditation. These guidelines are relevant to laboratory‐based testing only. These guidelines follow current best practices and are constantly under review. Abstract : These guidelines for Legally Defensible Workplace Drug Testing by use of oral fluid have been prepared and updated by the European Workplace Drug Testing Society (EWDTS). The European Guidelines are designed to establish best practice procedures whilst allowing individual countries to operate within the requirements of national customs and legislation. The EWDTS recommends that all European laboratories that undertake legally defensible workplace drug testing should use these guidelines as a template for accreditation.